A Dynamical Framework for Interpreting Ancient Sea Surface Temperatures. Issue 15 (3rd August 2020) - Judd, Emily J.; Bhattacharya, Tripti; Ivany, Linda C.
Abstract: Efforts to estimate past global mean temperature and latitudinal gradients must contend with spatial heterogeneity in sea surface temperatures (SSTs). Here, we use modern SSTs to show that the environments from which most paleoclimatic data are drawn, shallow epeiric seas and continental margins, are systematically offset from zonal mean temperatures. Epeiric seas are warmer and more seasonal than open‐ocean values from the same latitudes, while continental margins exhibit consistent and predictable deviations related to gyre circulation. Warm temperatures inferred from Paleozoic proxy data may largely reflect that these data derive almost entirely from epeiric seas. Moreover, pseudoproxy analysis using Paleogene sampling localities demonstrates how undersampling of the full range of dynamical environments associated with gyre circulation can generate spurious estimates of latitudinal temperature gradients. Recognition of these global patterns permits a predictive framework within which to more robustly interpret proxy data, improve Earth system models, and reconstruct ancient dynamic regimes. Plain Language Summary: Geochemical analyses provide estimates of past sea surface temperature. These data are integral to calculating global climate metrics, such as the latitudinal temperature gradient. For myriad reasons, the sites of these data are not evenly distributed across the global oceans but, instead, are biased toward two environments—continental margins and shallow continental seas. It is therefore important to determine the extent to which theses environments reflect broader climatic conditions. We use global ocean data to demonstrate that modern shallow, restricted seas are consistently warmer and more seasonal than anticipated for their given latitude. Because all sea surface temperature data older than ~200 Ma come from these environments, this observation could help explain why many Paleozoic temperatures appear unrealistically hot. Similarly, nearshore environments exhibit consistent offsets from the open ocean, both in terms of annual temperature and seasonal range, depending on their position within a gyre. This observation helps explain some of the longitudinal heterogeneity in paleoclimate data and should be used to inform locations to target for future data collection. Ignoring environment‐specific patterns can lead to spurious estimates of global climate metrics. However, cognizance of and correction for sampling location biases can improve interpretations of ancient climates. Key Points: Proxy‐derived estimates of past sea surface temperatures are biased toward epeiric seas in the Paleozoic and coasts in the Cenozoic In the modern ocean, sea surface temperatures from these environments systematically deviate from open ocean values at the same latitude These deviations, related to ocean dynamics, must be considered when reconstructing latitudinal gradients and assessing model fidelity